Optimization of Edge Banding Process Parameters Used for Particle Board and Medium Density Fiberboard - Kucuk Huseyin Koc; Ender Hazir; Sedanur Seker (BioResources)
This study determined the factors affecting peeling strength performance of edge bands, an important element of the furniture industry, and improved peeling strength performance by optimizing these factors. The independent variables were material types, amount of adhesive, feed speed, and temperature, while the dependent variable was the peeling strength. A central composite design (CCD) was used to investigate the optimal process parameters to achieve a maximum peeling strength for medium-density fiberboard (MDF) and particle board (PB). These materials were prepared using different feed speeds, temperatures, and amounts of adhesive. The CCD design based on the desirability function approach successfully achieved the optimal process parameters. An analysis of variance (ANOVA) determined the significant parameters on the peeling strength of edge banding. Maximum MDF and PB edge banding peeling strength values were calculated as 0.0706 and 0.0673 N/mm2, respectively. In the edge banding process applied using optimum parameter levels, an increase of 8.8% and 7.17% was achieved in the peeling strength of PB and MDF samples, respectively.